Unlocking Rural and Remote Coverage with Small Cells and Satellite - Abdullahi, U. S.; Longman, F. S.; Christopher, T. T.; Adesina, L. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
According to the Global System for Mobile Alliance (GSMA), in 2017, there were around 3.3 billion people connected to the mobile Internet. This represented an upward surge in global coverage compared to previous years. However, more than one billion people are still not covered by mobile broadband networks, representing what is termed “the coverage gap”. Uncovered populations typically live in rural locations with low population densities, low per-capita income levels and weak or non-existent enabling infrastructure, and thus, closing the mobile coverage gap seems to be more of an economic challenge, than a pure technical one. This paper presents an overview of the need for rural and remote coverage, both from an operator and consumer as well as government perspective. It then presents the major challenges, and necessary actions to be taken by industry, Government and other stake-holders to drive rural and remote coverage by significantly lowering the cost of network roll-out and increase incentives for such deployments. The paper therefore, presents a technical and business case for the use of “Small Cells” in conjunction with satellites with a view to opening up huge markets via collaboration between the mobile operators and satellite system owners, while offering significant improvements in the coverage and capacity needs of remote, rural or underserved end-users in a cost-effective and scalable manner. Detailed insights to these two technologies are presented, including the innovations to overcome technical and regulatory challenges. Lastly, some real-life deployments are given and the paper concludes with some recommendations for Government and network operators presented